Anorexia e o mal-estar na contemporaneidade - Paula, Alan Braga de (2010)
This article discusses the following questions: what are the structural aspects of anorexia? How anorexia is of the culture in the contemporary? Anorexia exposes a malaise of contemporary society? And if withdraws, that malaise is this? To develop this research I make use mainly of Psychoanalytic Theory, especially the Freudian concepts of body, desire, drive, anorexia and culture. I also make contributions in history, especially the contributions of Denize Bernuzzi Sant'ana on the contemporary, body and magreza.A methodology used for this research is to psychotherapy, since it proposes to investigate the uniqueness of the subject, while trained and entered in the field language and observed in the transference relationship between analyst and analysand. Therefore, this thesis begins with a chapter on anorexia as a symptom. Then discuss anorexia in more detail by addressing the psychological dynamics responsible for the formation of anorexic symptoms. Seeking me go a little deeper, I think the next chapter in what is the desire according to psychoanalysis and how it presents itself in the psychic dynamics of anorexics. Then I discuss the concept of body in psychoanalysis, to understand that this assumes the lead role in the dynamics anorexic. Then I try to introduce the concept of malaise presented by Freud in his famous book The malaise in Civilization (1930). Present soon after, reports of a young woman with anorexic symptoms posted on his blog on the internet during the period September 2006 to October 2009. Then discuss these reports from a psychoanalytic reading about the subjectivity of this young, where I try to analyze the unconscious material that these reports are likely to hide. I conclude with a discussion on the malaise related to anorexia, which I try to articulate the analysis of the text of young Anna Paula with psychoanalytic concepts about the contemporary and historical